2013
DOI: 10.5194/sd-16-1-2013
|View full text |Cite
|
Sign up to set email alerts
|

IODP Expedition 339 in the Gulf of Cadiz and off West Iberia: decoding the environmental significance of the Mediterranean outflow water and its global influence

Abstract: Abstract. IODP Expedition 339 drilled five sites in the Gulf of Cadiz and two off the west Iberian margin (November 2011 to January 2012), and recovered 5.5 km of sediment cores with an average recovery of 86.4 %. The Gulf of Cadiz was targeted for drilling as a key location for the investigation of Mediterranean outflow water (MOW) through the Gibraltar Gateway and its influence on global circulation and climate. It is also a prime area for understanding the effects of tectonic activity on evolution of the Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…This approach follows Bahr et al (2014) who showed that conditions at the sea surface drive the Br content at Site U1387 which is located in vicinity and similar water depth as Site U1386 (Fig. 1C, Hernández-Molina et al, 2013). It was argued that Br is not distinctly influenced by varying lithology and its variations are not directly linked to other elements, making it an excellent tool for stratigraphic correlation .…”
Section: Age Controlmentioning
confidence: 95%
See 1 more Smart Citation
“…This approach follows Bahr et al (2014) who showed that conditions at the sea surface drive the Br content at Site U1387 which is located in vicinity and similar water depth as Site U1386 (Fig. 1C, Hernández-Molina et al, 2013). It was argued that Br is not distinctly influenced by varying lithology and its variations are not directly linked to other elements, making it an excellent tool for stratigraphic correlation .…”
Section: Age Controlmentioning
confidence: 95%
“…As a water mass, the MOW can be traced within the Gulf of Cadiz in two major flow cores located at 800-1400 m water depth alongside the middle slope (lower MOW core), and at 500-700 m water depth alongside the upper slope including our study area (upper MOW core, Fig. 1B) (Baringer and Price, 1997;Borenäs et al, 2002;Hernández-Molina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Black triangles with numbers indicate biostratigraphic and palaeomagnetic tie points used, as referenced in Table 1. Black and white bar at the top represents core recovery following Hernández-Molina et al (2013). (b) Comparison of the benthic δ 18 O record of Site U1389 on a new timescale according to our tuning, and the benthic δ 18 O MedSea stack on its respective age model (Lourens et al, 2004).…”
Section: Grain-size Analysesmentioning
confidence: 99%
“…In the Gulf of Cadiz, MOW follows the topography of the continental shelf in two major flow cores at 800-1400 m water depth (lower MOW core) and 500-700 m water depth including our study area (upper MOW core,Fig. 1a) (Baringer and Price, 1997;Borenäs et al, 2002;Hernández-Molina et al, 2013). After exiting the Gulf of Cadiz, most of MOW flows north along the European continental margin until it mixes with the North Atlantic Current at Rockall Plateau (HernandezMolina et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…During the IODP Expedition 339, from November 2011 to January 2012, seven sites (Sites U1385-U1391) were drilled in the southwest margin of the Iberian Peninsula (Expedition 339 Scientists, 2013a;Hernández-Molina et al, 2013. IODP Site U1385, located on the West Iberian margin (37°34.285′ N, 10°7.562′ W, Fig.1), was drilled close to core MD01-2444 Voelker and de Abreu, 2011;Channell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%